Peran Good Governance dalam Meningkatkan Kualitas Pelayanan Publik: Perspektif Teoretis - Rahmawati, Noer Bunka; Tjenreng, Muhammad Baharuddin Zubakhrum (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aims to explore the role of good governance in improving the quality of public services. The quality of public services is highly dependent on the implementation of good governance principles, which include transparency, accountability, public participation, and effectiveness. In this research, the approach used is a qualitative method with a literature study to analyze existing literature regarding the implementation of good governance in public services. The results show that transparency and accountability have a very significant role in improving the quality of public services. Transparency allows the public to monitor and ensure that public policies and resources are managed properly. Accountability encourages the government to be responsible for its decisions and policies, thereby increasing public trust in the government. However, the implementation of good governance also faces a number of challenges such as complex bureaucracy, corruption, and limited human resource capacity. These challenges hinder the effectiveness of public services, even though the principles of good governance have been applied.